The inheritance of values in Sundanese song of Cianjuran in West Java - Julia, Julia; Supriyadi, Tedi (Harmonia: Journal of Arts Research and Education, 2017)
This article examines the issue of inheritance that occurs in the Sundanese Song of Cianjuran. During this time, the inheritance is dominated by the transfer of skills only, while the transfer of value tends to be ignored. Consequently, the public cannot grasp the value of what is important to Sundanese Song of Cianjuran, so that over time the Sundanese Song of Cianjuran being abandoned. Through research conducted by observation into the studio and the training venues of Sundanese Song of Cianjuran, and interviews with the artists of Sundanese Song of Cianjuran, the study results showed two things. First, the Sundanese Song of Cianjuran contains the value both in lyrics and music accompaniment, in the lyrics have meaning is quite diverse, whereas the musical accompaniment contains any value in the form of symbolic treatment. Second, the process of inheritance value, on the one hand, occurs at certain times through a casual chat after training Sundanese Song of Cianjuran finished, and on the other hand, the value of inheritance is one drawback in the regeneration of Sunda Cianjuran song, because teachers tend to pass on the skills aspect alone.